Ghrelin Protects against Dexamethasone-Induced INS-1 Cell Apoptosis via ERK and p38MAPK Signaling - Chengshuo Zhang; Le Li; Bochao Zhao; Ao Jiao; Xin Li; Ning Sun; Jialin Zhang (International Journal of Endocrinology)
Glucocorticoid excess induces apoptosis of islet cells, which may result in diabetes. In this study, we investigated the protective effect of ghrelin on dexamethasone-induced INS-1 cell apoptosis. Our data showed that ghrelin (0.1 μM) inhibited dexamethasone-induced (0.1 μM) apoptosis of INS-1 cells and facilitated cell proliferation. Moreover, ghrelin upregulated Bcl-2 expression, downregulated Bax expression, and decreased caspase-3 activity. The protective effect of ghrelin against dexamethasone-induced INS-1 cell apoptosis was mediated via growth hormone secretagogue receptor 1a. Further studies revealed that ghrelin increased ERK activation and decreased p38MAPK expression after dexamethasone treatment. Ghrelin-mediated protection of dexamethasone-induced apoptosis of INS-1 cells was attenuated using the ERK inhibitor U0126 (10 μM), and cell viability increased using the p38MAPK inhibitor SB203580 (10 μM). In conclusion, ghrelin could protect against dexamethasone-induced INS-1 cell apoptosis, at least partially via GHS-R1a and the signaling pathway of ERK and p38MAPK.